Antwortsicherheiten: Indikatoren für das Selbstkonzept von Grundschulkindern? - Fritzsche, Eva; Kröner, Stephan (76. Tagung der Arbeitsgruppe für Empirische Pädagogische Forschung (AEPF), 2011)

Antwortsicherheit von Grundschulkindern: ein Maß für das Selbstkonzept? - Fritzsche, Eva (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)

Bereichsspezifische Determinanten außerschulischer musikalischer Aktivitäten von Grundschulkindern - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (Beiträge Empirischer Musikpädagogik, 2017)
Warum spielen manche Grundschulkinder ein Musikinstrument oder singen im Chor und andere nicht? Bisherige Studien zu musikalischen Aktivitäten sind größtenteils deskriptiv angelegt oder basieren auf eingeschränkten Operationalisierungen. Vor dem Hintergrund eines theoretischen Rahmenmodells haben wir Skalen zu den bereichsspezifischen Determinanten außerschulischer musikalischer Aktivitäten (intrinsischer Aspekt der Einstellung, injunktive und deskriptive subjektive Norm und musikalisches Selbstkonzept) entwickelt und pilotiert (N = 193 Viertklässler). Alle bereichsspezifischen Determinanten korrelierten statistisch signifikant mit dem Ausmaß außerschulischer musikalischer Aktivitäten. Im Strukturgleichungsmodell wiesen sowohl die deskriptive subjektive Norm bezogen auf die Eltern als auch der intrinsische Einstellungsaspekt, vor allem aber das musikalische Selbstkonzept einen eigenständigen Erklärungswert auf (68 % Varianzaufklärung). Das höhere Aktivitätsniveau der Mädchen wurde vollständig durch die bereichsspezifischen Determinanten vermittelt. Die Skalen können künftig genutzt werden, um Effekte von Maßnahmen für die Förderung musikalischer Aktivitäten bei Grundschulkindern zu evaluieren. Why do some primary school students play an instrument or sing in a choir and others do not? Most previous studies were either descriptive reports on musical activities or they were limited in the operationalization of the determinants. Thus, based on a theoretical framework, we developed and tested scales for the assessment of musical leisure time activities and their domain-specific determinants (musical self-concept, injunctive and descriptive subjective norm, intrinsic aspect of attitude) in N=193 fourth graders. All domain-specific determinants showed statistically significant correlations with musical leisure time activities. In a structural equation model, both descriptive norm relating to parents and intrinsic aspect of attitude and in particular the musical self-concept dis-played unique explanatory value for musical activities (68% variance explanation). Slightly higher activity levels of girls were completely mediated by the domain-specific determinants. In future studies, the developed scales may be applied for the evaluation of interventions fostering musical activities in primary school childre
Keywords: Freizeitaktivität; Grundschulkinder; Motivation; musikalisches Selbstkonzept; musikalische Aktivitäten; musikalische Praxis

Choirboys and other academic-track students - Determinants of musical activities at academic-track schools with different profiles - Fritzsche, Eva (International Conference on Motivation, 2012)

Chorknaben und andere Gymnasiasten - Determinanten musikalischer Aktivitäten an Gymnasien mit unterschiedlichen Schulprofilen - Fritzsche, Eva; Kröner, Stephan; Pfeiffer, Wolfgang (Journal for educational research online, 2011)
Wovon hängt es ab, wie musikalisch aktiv Gymnasiastinnen und Gymnasiasten sind? Der Theorie des geplanten Verhaltens zufolge sollten der intrinsische Wert als Aspekt der Einstellung, die musikalische Affinität von Freunden und Eltern als Aspekt der subjektiven Norm und das musikalische Selbstkonzept als Aspekt der wahrgenommenen Verhaltenskontrolle relevante Prädiktoren musikalischer Aktivitäten sein. Ebenfalls relevant dürfte die Musikbezogenheit des Profils der besuchten Schule sein. Dies wurde anhand von N = 2016 musikalisch aktiven Gymnasiasten überprüft. Mittels Mehrgruppen-Strukturgleichungsmodellen wurden Jungen an nicht ausgeprägt musischen Gymnasien als Referenzgruppe mit Mädchen derartiger Gymnasien und mit Jungen an ausgeprägt musischen Gymnasien verglichen. Erwartungsgemäß wiesen die Jungen an ausgeprägt musischen Gymnasien gegenüber der Referenzgruppe im Mittel höhere musikalische Affinitäten von Freunden und Eltern und umfangreichere musikalische Aktivitäten auf. Innerhalb der Gruppen zeigten sich uneinheitliche Effekte der Prädiktoren. Implikationen für Effekte von Schulprofilen auf die Förderung musikalischer Aktivitäten werden diskutiert. <br

Confidence in primary school students: A measure for self-concept? - Fritzsche, Eva (Metacognition, 5th Biennial Meeting of the EARLI Special Interest Group 16, 2012)

Confidence in primary school students: A measure for self-concept? - Fritzsche, Eva (16th Conference of Junior Researchers of EARLI (JURE), 2012)

Confidence scores as measures of metacognitive monitoring in primary students? (Limited) Validity in predicting academic achievement and the mediating role of self-concept - Fritzsche, Eva; Kröner, Stephan; Dresel, M.; Kopp, Bärbel; Martschinke, Sabine (Journal for educational research online, 2012)

Das musikalische Selbstkonzept als bedeutsame Determinante musikalischer Freizeitaktivitäten bei Grundschulkindern - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (15. Fachgruppentagung Pädagogische Psychologie (PAEPS), 2015)

Determinanten musikalischer Aktivitäten im Grundschulalter. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (Perspektiven der Forschung zur kulturellen Bildung ; Dokumentation der Fachtagung am 6. und 7. Juni 2013 in Berlin, 2013)

Determinants of musical activities in primary school children. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (ZiLL-Herbsttagung, 2012)

Determinants of musical activities in primary school students. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (18. Conference of Junior Researchers of EARLI (JURE), 2014)

Effects of intensive musical practice on secondary male students' behavior and personality - Fritzsche, Eva (17th Conference of Junior Researchers of EARLI (JURE), 2013)

Elternengagement, Schulklima und Werte aus Sicht von Elternvertretern und Schulleitungen - eine Fragebogenerhebung. - Fritzsche, Eva; Kröner, Stephan; Friedrich, Marcus C. G. (Elternvertreter mit Migrationshintergrund an Schulen, 2009)

Elternvertreter mit Migrationshintergrund an allgemeinbildenden Schulen – eine qualitative Interviewstudie zu ihren Beweggründen für und gegen ein Engagement - Kröner, Stephan; Schüller, Elisabeth; Penthin, Marcus; Fritzsche, Eva; Friedrich, Marcus C. G.; Krol, Magdalena (Zeitschrift für Erziehungswissenschaft, 2012)
Eltern mit Migrationshintergrund sind in Elternvertretungen an Schulen in Deutschland unterrepräsentiert. Ein stärkeres Engagement dieser Eltern ist jedoch im Sinne gelebter demokratischer Kultur unverzichtbar. Um das Spektrum der Beweggründe von Eltern mit Migrationshintergrund für und gegen ein Engagement auszuloten, wurden Interviews mit N = 31 engagierten Eltern mit Migrationshintergrund geführt und ausgehend von Kategorien der Theorie des geplanten Verhaltens inhaltsanalytisch ausgewertet. Die Kategorie „Einstellung“ wurde hierzu deduktiv in „Motivation im Handlungsvollzug/intrinsischer Wert“, „Ergebnisse und Folgen bzgl. eigener Belange“ und „Ergebnisse und Folgen für Andere/altruistische Erwägungen“ untergliedert. Die „subjektive Norm“ wurde induktiv in „andere Eltern“, „Lehrkräfte und Schulleitung“ und „sonstige Personen/wahrgenommene allgemeine Erwartungshaltung“ ausdifferenziert und die „wahrgenommene Verhaltenskontrolle“ in Unterkategorien zu „Selbstvertrauen und Angstfreiheit“, „sprachlicher Kompetenz“, „sozioökonomischem Hintergrund“, „Verfügbarkeit von Zeit“, „Setting in Schule und Sprengel“ und „Feldkompetenz und Sachkenntnis“. Zusätzlich wurde „Gewohnheit“ als Hauptkategorie deduktiv gesetzt und beibehalten. Für insgesamt 513 analysierte Aussagen ergab sich eine Beurteilerübereinstimmung von κ = 0.82. Implikationen für die interkulturelle Elternarbeit werden diskutiert. Parents with a migration background are underrepresented among parent representatives at schools in Germany. However, increased involvement of these parents is essential for a lively democratic culture. To explore the motivations of parents with migration background regarding their school involvement, interviews with N = 31 parent representatives with migration background were content analysed, starting deductively from a set of categories according to the theory of planned behaviour. In the analysis, the main category “attitude” was deductively subdivided into “motivation in the course of action/intrinsic value”, “results and consequences regarding own interests” and “results and consequences regarding others/altruistic motivation”. “Subjective norm” was inductively differentiated into “other parents”, “teachers and leadership team” and “other persons/perceived general expectations”; “perceived behavioural control” was differentiated into the subcategories “assertiveness and freedom from anxiety”, “language competence”, “socioeconomic background”, “availability of time”, “setting in school and school district” and “field expertise and know-how”. Additionally, “habit” was deductively established and retained as a main category. Analysis of 513 statements resulted in an interrater-agreement of κ = 0.82. Implications for working with parents in an intercultural context are discussed.<br
Keywords: Elterliches Engagement; Elternbeteiligung; Partizipation; Demokratie; Einstellungen

Elternvertreter mit Migrationshintergrund: Gründe für das Engagement, Strategien und Schwerpunkte der Arbeit, Probleme und Verbesserungsvorschläge - eine qualitative Interviewstudie - Kröner, Stephan; Fritzsche, Eva; Friedrich, Marcus C. G. (Elternvertreter mit Migrationshintergrund an Schulen, 2009)

Empfehlungen zur Verbesserung der Zusammenarbeit zwischen Schulen und Eltern mit Migrationshintergrund - Kröner, Stephan; Friedrich, Marcus C. G.; Fritzsche, Eva (Elternvertreter mit Migrationshintergrund an Schulen, 2009)

"Es geht mir nicht darum, möglichst schnell fertig zu werden, sondern möglichst viel aus meinem Studium mitzunehmen." Gründe für die Überschreitung der Regelstudienzeit aus Studierendensicht - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (5. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF), 2017)

Gründe für die Überschreitung der Regelstudienzeit aus Studierendensicht - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (Beiträge zur Hochschulforschung, 2017)
Over half of students at German universities exceed the specified course duration. The underlying reasons have not been investigated thoroughly. Therefore, the aim of this study was to develop a classification system for their assessment. A set of categories, derived from literature, has been refined within the process of a qualitative content-analysis, on the basis of statements from an open answer option of a student survey. The main resulting categories were “system level”, “intra-university factors (course aspects)”, “individual characteristics and initial requirements of students”, “personal situation of students and contextual factors” and “other problems during specific situations in a course”. It becomes evident that exceeding the specified course duration is not necessarily negative. This set of categories can serve as a starting point for developing a questionnaire structure to elucidate the reasons for exceeding the specified course duration. Über die Hälfte der Studierenden an deutschen Hochschulen überschreitet die Regelstudienzeit. Um die bisher meist nur ausschnittsweise betrachteten Ursachen zu systematisieren, wurde in dieser Arbeit ein aus der Literatur abgeleitetes Kategoriensystem entwickelt, das bis zu drei Gliederungsebenen umfasst. Grundlage war die qualitativ-inhaltsanalytische Auswertung offener Aussagen Studierender auf die Frage nach den Gründen der Überschreitung ihrer Regelstudienzeit. Es konnten die Hauptkategorien „Systemebene“, „hochschulinterne Faktoren (Studienbedingungen)“, „individuelle Merkmale und Eingangsvoraussetzungen“, „persönliche Lebensbedingungen und Kontextfaktoren“ sowie „sonstige Probleme bei spezifischen Situationen eines Studiums“ gebildet werden. Deutlich wird, dass eine Überschreitung der Regelstudienzeit im Sinne einer über die Prüfungsordnung hinausgehenden Bildung nicht per se negativ zu werten ist. Das Kategoriensystem ist ein geeigneter Ausgangspunkt für die Generierung einer Fragebogenskala zur Erhebung von Gründen für die Überschreitung der Regelstudienzei
Keywords: Regelstudienzeit; Hochschule; Bildungsqualität; Studiendauer; Studierende

Gründe für die Überschreitung der Regelstudienzeit - Entwicklung eines Kategoriensystems. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (1. Tagung der Gesellschaft für Empirische Bildungsforschung, 2013)

Lehrveranstaltungen evaluieren: Impulse aus der Forschung für eine gute Praxis - Fritzsche, Eva; Kröner, Stephan (Hochschuldidaktische Aufsätze der Infothek Lehre, 2015)

Mechanismen bei der Vergabe (meta-)metakognitiver Urteile von Studierenden - Fritzsche, Eva; Händel, Marion (Zentralinstitut für Lehr-Lernforschung (ZiLL), Jahrestagung, 2013)

Musical elite gymnasia as learning environments and settings for personality development in secondary students? The case of musical self-concept. - Fritzsche, Eva; Pfeiffer, Wolfgang; Kröner, Stephan (Psychological Test and Assessment Modeling, 2015)
Elite gymnasia with a main focus on musical education are special institutional learning environments for the students attending those schools: Their curricula differ considerably from those of non-specialized schools regarding the emphasis that is placed on musical activities. Thus, if effects of intensive musical education on personality development proposed in musical education research are to be found, then examining students from such elite schools seems pertinent. However, beyond institutional impact, effects of variables from the students’ individual learning environment are to be expected. Thus, reanalysing data from Bernecker, Haag and Pfeiffer (2006), we investigated effects of both the institutional and the individual learning environment on different facets of the self-concept of ability with n = 509 students from 91 classes including class-levels 5 to 10 (corresponding to an age of 10 to 16 years). Classes we re located either at musical elite gymnasia providing intensive musical education and including the opportunity to participate in an internationally recognised choir or at non-specialized gymnasia without such an elite musical profile. As expected, multilevel analyses revealed strong effects of school type (i.e., institutional effects) on musical activities. However, in line with Schellenberg (2006), our results did not provide evidence either for substantial institutional effects on the musical self-concept, or for such effects on the academic or general self-concept. Rather, variance in self-concept facets could better be explained via aspects of the individual learning environment or by personal characteristics like school grades or the intrinsic value of musical activities. The implications for potential effects of attending a musical elite gymnasium on personality development as well as avenues for further research are discusse

Musical Leisure Activities in Elementary School Students: The Role of Music-Related Beliefs, Sex, Socioeconomic Status, and Migration Background - Penthin, Marcus; Birnbaum, Lisa; Fritzsche, Eva; Kröner, Stephan (SAGE Open, 2025)
The present study aims to investigate the effects of music-related beliefs on musical leisure activities of elementary school students. To this end, the relationship between music-related beliefs and musical leisure activities was examined while controlling for sex, socio-economic status, and migration background. Data analyses are based on a survey-based study conducted with n = 685 fourth-graders in Germany. Sex and socioeconomic status, but not migration background, explained a small amount of variance in musical leisure activities. After including the music-related beliefs as predictors, they completely mediated the effects of domain-general variables on musical leisure activities and explained 77% of variance in musical leisure activities, with all predictors except the intrinsic value showing unique effects. This work further contributes to the development of reliable and valid scales for the assessment of music-related beliefs. When considering avenues for further research, we emphasize that it is important to incorporate a broad range of music-related beliefs as determinants of leisure musicking in childre
Keywords: beliefs; elementary school children; extracurricular activities; leisure-time activities; musical self-concept; musicking

Prüfen in der Hochschullehre: Impulse aus der Forschung für eine gute Praxis - Fritzsche, Eva; Kröner, Stephan (Hochschuldidaktische Aufsätze der Infothek Lehre, 2015)

Schulklima und Werte aus Sicht von Elternvertretern und Schulleitungen - eine Fragebogenerhebung - Fritzsche, Eva; Kröner, Stephan; Friedrich, Marcus C. G. (Elternvertreter mit Migrationshintergrund an Schulen, 2012)

Students' confidence in their performance judgements: a comparison of different response scales - Händel, Marion; Fritzsche, Eva (Educational Psychology, 2015)
We report results of two studies on metacognitive accuracy with undergraduate education students. Participating students were asked to judge their personal performance in a multiple-choice exam as well as to state their confidence in their performance judgement (second-order judgement [SOJ]). In each study, we compared four conditions that differed in the type of the presented 5-point confidence scale for SOJs. In Study 1, four bipolar scales with different labels were applied; in Study 2, unipolar and bipolar scales were implemented. The results of Study 1 with N = 420 students show that undergraduates on average provided accurate performance estimations. However, students were not aware of their judgement accuracy, shown by a low fit of SOJ and judgement accuracy. In addition, the type of provided scale significantly influenced the SOJs. Study 2 with N = 348 students replicated the findings of the first study and gave further insight into the effects of uni- vs. bipolar response scales.
Keywords: second-order judgements; response scales; undergraduates; metacognitive accuracy

Systematische Erhebung der Gründe für eine Überschreitung der Regelstudienzeit - Weiterentwicklung eines bestehenden Fragebogens durch die Auswertung offener Antworten. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (ZiLL-Jahrestagung, 2015)

The musical self-concept as a determinant of musical leisure time activities in primary school students. - Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (8th SELF Biennial International Conference, 2015)

Unskilled but subjectively aware: Metacognitive monitoring ability and respective awareness in low-performing students - Händel, Marion; Fritzsche, Eva (Memory and Cognition, 2016)
Two studies were conducted to further examine the unskilled-and-unaware effect and to test whether low-performing students are indeed unaware of their (expected) lower metacognitive monitoring abilities. Postdicted judgments of performance and second-order judgments (SOJs) were solicited to test students’ metacognitive awareness. Given that global and local judgments tend to differ (the confidence–frequency effect), we investigated whether students’ (un)awareness pertains to both types of judgments. A first study focusing on global judgments was conducted in a regular exam setting with 196 undergraduate education students. A second study with 115 undergraduate education students examined both global and local judgments. Local judgments were analyzed on an average level and according to different signal detection theory categories (hits, correct rejections, misses, and false alarms). In both studies, students were grouped in four performance quartiles. The results showed that low-performing students highly overestimated their performance (they were functionally overconfident). However, their SOJs indicated that they were less confident in their judgments than the other students, and thus seemed to be aware of their low ability to estimate their own performance (they were not subjectively overconfident). This was observed for global as well as for averaged local SOJs. Moreover, an analysis of the local judgments revealed that students’ SOJs varied depending not only on whether their judgments were accurate but also on whether or not they thought they knew the answer to an item. In sum, SOJs provide valuable information about students’ metacognitive awareness.
Keywords: Global judgments; Local judgments; Metacognition; Performance judgments; Second-order judgments

Wer riskiert eine Mahnung? Zur Validierung der NEO-PI-R-Gewissenhaftigkeitsskala und ihrer Facetten mit Hilfe von Verhaltensspuren für dispositionelle Selbstregulation - Kröner, Stephan; Fritzsche, Eva (Diagnostica, 2012)
Inwieweit kann Gewissenhaftigkeit nach dem NEO-PI-R auf Faktor- und Facettenebene zur Diagnostik der dispositionellen Selbstregulation herangezogen werden? Wir haben dies exemplarisch anhand einer Handlung mit hohen Selbstregulationserfordernissen untersucht: dem Ausleihen, fristgerechten Durcharbeiten und pünktlichen Zurückgeben von Bibliotheksbüchern. Defizite in der Handlungsregulation wurden dabei als Verhaltensspur über Einträge in der Bibliotheksdatenbank erhoben. Über die NEO-PI-R-Skala Gewissenhaftigkeit und ihre Facetten hinaus wurden damit verwandte Skalen für Selbstkontrollkapazität und Prokrastination als Prädiktoren verwendet. Ergebnisse einer Untersuchung mit N = 99 Bibliotheksnutzern zeigen, dass die Gewissenhaftigkeitsfacette Selbstdisziplin einen substantiellen Erklärungswert für das Vorliegen von Mahnungen aufweist. Skalenwerte für die übrigen Gewissenhaftigkeitsfacetten, für Prokrastination und für Selbstkontrollkapazität wiesen demgegenüber keinen eigenständigen Erklärungswert auf. Konsequenzen für die diagnostische Anwendung der verwendeten Skalen werden diskutiert.<br
Keywords: Selbstkontrolle; Selbstregulation; Skala; Persönlichkeit; NEO Personality Inventory; self-control; self-regulation; scale; personality; NEO Personality Inventory

What do second-order judgments tell us about low-performing students’ metacognitive awareness? - Fritzsche, Eva; Händel, Marion; Kröner, Stephan (Metacognition and Learning, 2018)

Who plays a musical instrument in elementary school? The explanatory value of the family economic and cultural capital in the musical domain. - Wießnet, Verena; Penthin, Marcus; Fritzsche, Eva; Kröner, Stephan (Beiträge Empirischer Musikpädagogik, 2018)
Playing a musical instrument requires economic capital and represents cultural capital. Thus, the odds to play an instrument are low for children from low-capital families. Moreover, if low-capital children are musically active, they should choose instruments providing lower distinction values. We investigated how economic capital (via highest International Socioeconomic Index of Occupation, HISEI) and music-related cultural capital (via parental musical activity) act together in explaining (a) whether children play any instrument and (b) explain the choice of classical vs. other vs. no instrument. We surveyed N = 685 students (Mage = 9.88, SD = 0.52, 50 % girls) from 16 elementary schools. Logistic regression (χ2 (2) = 93.94, p ≤ .01, n = 653; correctly classifying 60 % of the cases) showed that the odds of child musical activity increased both with parental HISEI (odds ratio for HISEI = 1.03, Wald χ2 (1) = 29.59, p ≤ 01) and parental musical activity (odds ratio = 3.02, Wald χ2 (1) = 35.70, p ≤ .01). Moreover, playing an instrument related to classical music was associated with both a higher parental HISEI (F(2, 659) = 33.95, p < .001; η2 = .09) and parental musical activity. Implications of our results for equal access to musical activities are discussed.<br
Keywords: cultural capital; economic capital; musical instrument; elementary school children